The Diverse Roles of 17β-Estradiol in Non-Gonadal Tissues and Its Consequential Impact on Reproduction in Laying and Broiler Breeder Hens - Hanlon, Charlene; Ziezold, Clara J.; Bédécarrats, Grégoy Y. (Frontiers in Physiology, 2022)
Estradiol-17β (E2) has long been studied as the primary estrogen involved in sexual maturation of hens. Due to the oviparous nature of avian species, ovarian production of E2 has been indicated as the key steroid responsible for activating the formation of eggshell and internal egg components in layer-type hens. This involves the integration and coordination between ovarian follicular development, liver metabolism and bone physiology to produce the follicle, yolk and albumen, and shell, respectively. However, the ability of E2 to be synthesized by non-gonadal tissues such as the skin, heart, muscle, liver, brain, adipose tissue, pancreas, and adrenal glands demonstrate the capability of this hormone to influence a variety of physiological processes. Thus, in this review, we intend to re-establish the role of E2 within these tissues and identify direct and indirect integration between the control of reproduction, metabolism, and bone physiology. Specifically, the sources of E2 and activity in these tissues via the estrogen receptors (ERα, ERβ, GPR30) is described. This is followed by an update on the role of E2 during sexual differentiation of the embryo and maturation of the hen. We then also considering the implications of the recent discovery of additional E2 elevations during an extended laying cycle. Next, the specific roles of E2 in yolk formation and skeletal development are outlined. Finally, the consequences of altered E2 production in these layer-type hens and the associated disorders are discussed. While these areas of study have been previously independently considered, this comprehensive review intends to highlight the critical roles played by E2 to alter and coordinate physiological processes in preparation for the laying cycle.